Implementation of Additive Manufacturing in Designing A Wrist Hand Orthosis to Increase Grasping Time on The Left Hand of Cerebral Palsy Children - Julius Pandu Winata Manurung; Hari Setyanto; Lobes Herdiman (Jurnal Ilmiah Teknik Industri, 2021)
Cerebral palsy (CP) is a physical disability in childhood with impaired development of movement and posture due to disorders of the fetal or infant's brain. The measurement results of the spastic HCP children at YPAC Surakarta show that 8 attributes have difficulty grasping the precision type and 9 attributes of the power type. To solve this problem, hand tools called wrist hand orthoses are needed to restore hand function. This study aims to design alternative designs and make prototypes of wrist hand orthoses using the 3D printing process. The research stages began by collecting activity daily living (ADL) data and anthropometric data, taking a participatory approach to produce design alternatives, selecting design alternatives with the PUGH's concept selection method. The chosen design alternative will be printed through the additive manufacturing process. Testing with the 2015 human grasping database showed an increase in grasping time in 13 types of ADL activities from 17 ADLs.